School counseling and the student athlete : college, careers, identity, and culture - Zagelbaum, Adam (New York : Routledge, 2014)
'School Counseling and the Student Athlete explores empirical, theoretical, and practice-based issues that demand consideration by school-based counseling and educational professionals working at the pre-collegiate level. In its pages clinicians and students will find insights into both why student athletes experience many of the issues they do as well as the steps that counselors can take to help these individuals and their families. Theories of motivation and theoretical approaches to counseling student athletes are covered in order to provide an orientation to working with this group, and the book also includes a thorough discussion of the most important elements of counseling the student athlete: the academic, career, personal, and social issues they face; consultations with coaches, teachers, and parents; commercialism and the student athlete's identity; and gender, sexual identity, and culture issues. Each chapter ends with discussion questions and available resources for counselors. Grounded in research and pioneering in its analysis of sports psychology for students in grades K-12, School Counseling and the Student Athlete is a must-have book for school counselors, clinicians, and other professionals who work with elementary and secondary students.'--
Orientation to working with student athletes -- Theories of motivation and student development -- Commercialism and the identity of the student athlete -- Theoretical approaches of counseling the student athlete -- Family approaches to counseling the student athlete / Michale P. Hagan -- Gender, sexual identity, cultural issues, and the student athlete / Robyn Brammer -- Consultation with teachers and the student athlete -- Consultation with coaches and the student athlete -- Consultation with parents and the student athlete -- Academic issues for the student athlete -- Career and college issues for the student athlete / Gregg Kuehl -- Personal and social issues for the student athlete -- The transitional student athlete: movement away from sport / Carmen Wandel and Adam Zagelbaum -- The future of student athletics and school-based counseling services.
Includes bibliographical references and index.
Keywords: High school athletes -- Counseling of -- United States; High school athletes -- Education -- United States